Ecological Concerns in the Select Short Stories of Ruskin Bond: Exploring the link between nature and human existence in Ruskin Bond's short stories (Journal of Advances and Scholarly Researches in Allied Education, 2021)
I am able to claim a relationship with the trees, wild flowers, even the rocks that are an integral part of it. Yesterday, at twilight, when I passed beneath a canopy of oak leaves, I felt that I was a part of the forest. I put my hand and touched the bark of an old tree, and as I turned away, its leaves brushed against my face, as if to acknowledge me.Rain in the Mountains (197)The term Ecocide is derived from the Latin word 'Oikos meaning house or home and the Latin word 'Caedere' meaning strike down or demolish, wipe out or devastate. The literal meaning is to annihilate home or house. In the context of nature, it can be defined as the eradication or extermination of ecology and the environment. Uttarakhand is suffering from massive ecological destruction such as deforestation, extinction of wildlife, drying up natural resources of water, demolition of mountains, pollution of our great rivers like Ganges and Yamuna, rising of temperature, and consequently spreading of diseases like malaria, flood, and untimely rain. The great rivers of India the Ganga and Yamuna no longer carry the life rejuvenating water, they have been declared dead by the experts. So many long-lasting and aged are being cut for widening the roads and commercial purposes, mostly for mercenary benefits jeopardizing human and nonhuman life forms.